Jordanian’s Gulf Positions vis-a-vis the Syrian Crisis - Sultan Lotah, Maryam (Opción, 2019)
The study aims to investigate Jordanian’s Gulf Positions vis-a-vis the Syrian Crisis via comparative qualitative research methods. As a result, Jordanian policy guided by the Jordanian Monarch King Abdullah the Second has borne fruit by keeping Jordan secure and stable in the shadow of a flammable and conflict-ridden environment. In conclusion, Jordan adopted the Syrian crisis policy of buying time- awaiting the direction of events in the diplomatic and military aspects without angering its Gulf or American allies.